Inhibition of Notch1 Signaling at the Subacute Stage of Stroke Promotes Endogenous Neurogenesis and Motor Recovery After Stroke - Hao, Xiao-Zhu; Yin, Le-Kang; Tian, Jia-Qi; Li, Chan-Chan; Feng, Xiao-Yuan; Yao, Zhen-Wei; Jiang, Min; Yang, Yan-Mei (Frontiers in Cellular Neuroscience, 2018)
Background and purpose: It is still not clear whether Notch1 signaling inhibition can promote functional outcomes after stroke, given that it plays time-dependent roles in the sequential process of endogenous neurogenesis. The purpose of this study was to identify the appropriate time frame for Notch1 signaling inhibition according to the temporal evolution of Notch1 signaling activation and the responses of neural stem cells (NSCs), in order to target it for therapeutic intervention and stimulate neurorestorative strategies after stroke. Methods: Sprague-Dawley (SD) rats were subjected to 90-minutes of middle cerebral artery occlusion (MCAO). Rats were sacrificed before, and at day 1, day 2, day 3, day 4, and day 7 after ischemia for immunohistochemical analysis of the Notch intracellular domain (NICD), Nestin and doublecortin (Dcx). Next, MCAO rats were treated with the γ-secretase inhibitor N‐[N‐(3,5‐di uorophenacetyl)‐1‐alanyl]‐S‐phenylglycine t-butylester (DAPT) or with saline at day 4 after ischemia, and subsequently evaluated with behavioral test analysis and magnetic resonance imaging (MRI). The rat brains were then harvested for immunohistochemical analysis of Dcx, NeuN and myelin basic protein (MBP) at 2 weeks, 3 weeks, 4 weeks, and 8 weeks. Results: Notch1 signaling was maximally activated at day 3 after ischemia in parallel with the temporal evolution of NSCs. Inhibiting Notch1 signaling at day 4 after reperfusion with DAPT further promoted recovery of MRI parameters of the corticospinal tract (CST) and the functional outcomes, concomitantly with an increase in neuroblasts, their migration to the ischemic boundary, and potential differentiation to mature neurons, as well as the amelioration of axonal bundle integrity. Conclusions: Inhibition of Notch1 signaling at the subacute stage of stroke could maximally promote endogenous neurogenesis and axonal reorganization.